2023
DOI: 10.1039/d2cp04621k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ni atomic fraction on active species of graphene growth on Cu–Ni alloy catalysts: a density functional theory study

Abstract: Cu-Ni alloys are promising catalysts for precisely controlling the number of graphene layers grown by chemical vapor deposition (CVD). However, the theoretical understanding of the effect of the Ni atomic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…This result is acceptable because our previous study showed that alloying with Ni atoms can reduce the adsorption energy of the C monomer on the surface of the Cu(111) catalyst. 31 Hence, we justify the validity of the adsorption energy calculation procedure in this study. Furthermore, Table 1 shows that the adsorption of a C monomer on the subsurface results in a lower adsorption energy than that of adsorption at the interface.…”
Section: Segregation and Diffusion Into Processes Of C Adatomsmentioning
confidence: 60%
See 4 more Smart Citations
“…This result is acceptable because our previous study showed that alloying with Ni atoms can reduce the adsorption energy of the C monomer on the surface of the Cu(111) catalyst. 31 Hence, we justify the validity of the adsorption energy calculation procedure in this study. Furthermore, Table 1 shows that the adsorption of a C monomer on the subsurface results in a lower adsorption energy than that of adsorption at the interface.…”
Section: Segregation and Diffusion Into Processes Of C Adatomsmentioning
confidence: 60%
“…27,28,30 Therefore, the C monomer population is higher than other carbon source species under growth conditions (T = 1300 K, p Hd 2 = 0.01 Torr). 31 In addition, a transformation of the active species from C monomers on the catalyst surface to C monomers on the catalyst subsurface was observed when the Ni atomic fraction increased. 31 This condition is related to the decreased activation energy of the bulk diffusion of the C atom when the Ni atomic fraction is increased.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations